Relações étnico-raciais e o ensino de ciências nos anos iniciais do ensino fundamental: vivências e percepções em uma escola da rede pública de Sergipe - Santos, Maria Paula de Melo (2023)
Statistical data and academic research have highlighted the persistent ethnic-racial inequalities established and perpetuated in Brazilian society since the centuries-old process of colonization and the colonialist practices characterizing this process, up to the present day (IBGE, 2019; VERRANGIA, 2009). This process is perpetuated by structural racism, rooted in coloniality, which emerged in the sixteenth century when Europe, Africa, and the Americas converged on American territory (QUIJANO, 1992). It is this rationality that continues to sustain and reproduce prejudiced and discriminatory relations, various forms of subordination of knowledge and people, exclusion, and inequalities in different social spheres (LIMA, 2002; ALMEIDA, 2019, among others). In this regard, according to research, education also serves as a space for the reproduction of exclusions and prejudices, but also for their counteraction, as evidenced by the struggles of the Black Movement, both as claimants of essential rights and as educators throughout history (GOMES, 2012; LIMA; TRINDADE, 2009; GOMES; JESUS, 2013; GOMES, 2017). In this context, the approval of Law No. 10639/2003, which makes it mandatory to include African and Afro-Brazilian history and culture in the entire school curriculum (BRASIL, 2003), and the National Curricular Guidelines for Ethnic-Racial Relations Education - DCNERER (BRASIL, 2004) is significant. Within this context, this study poses the following problem: How has EthnicRacial Relations Education (ERER) been addressed in science education? With the general objective of analyzing how ERER has been addressed in science education in a 5th-grade class of a public school in Sergipe, in accordance with Law No. 10639/2003 and its guidelines. This is a qualitative research study, an ethnography of school practice (ANDRÉ, 2005), whose procedures include: conducting interviews with the class teacher and the school pedagogue; administering questionnaires and pedagogical activities (workshops) with the children in the class, as well as participant observation of lessons. The study indicates that, despite advances in academic and didactic production related to ERER, work related to science education, especially at the foundational level of education for children and youth, still requires politicalpedagogical investment, both in terms of teaching materials and pedagogical practices. These aspects underscore the ongoing need for greater investment in the implementation of ERER, especially in initial and ongoing teacher training.